Comparison of aortic diameter in normal subjects and patients with systemic hypertension - Jakrapanichakul, Decho; Chirakarnjanakorn, Srisakul (Journal of the Medical Association of Thailand, 2011)
Standard aortic root dimensional measurement by the two dimensional echocardiography should be routinely performed in all patients. There is limited data on the normal reference on Thai population. Aims of this study were (1) to determine the normal reference of aortic root dimension in Thai population and (2) to determine the difference in the aortic root size in patients with hypertension comparing with normal population. We retrospectively reviewed 81 patients who had the transthoracic echocardiographic examinations in our echocardiographic lab and had the aortic root measurement data. The patients with ascending aortic aneurysm, aortic dissection, aortic stenosis and/or regurgitation more than mild in degree, Marfan's syndrome and annuloaortic ectasia were excluded. The echocardiographic data of were collected; the aortic root dimensions at four levels; aortic valve annulus, sinus of Valsava, sinotubular junction and tubular parts. Hypertension was indentified if the patient had the prior diagnosis of hypertension and on antihypertensive medications, or who had blood pressure more than 140/90 mmHg for two or more occasions. Eighty-one patients were enrolled. Sixty patients (74.1%) were diagnosed hypertension. Mean age was 66.9 +/- 11.2 years in hypertensive patients and 49.1 +/- 16.4 years in normotensive patients. Normal reference values based on 95% upper normal limit of aortic valve annulus, sinus of Valsava, sinotubular junction and tubular part were 2.30 (2.21-2.38), 3.56 (3.35-3.77), 2.79 (2.61-2.97), and 3.36 (3.13-3.59), respectively. Patients with hypertension had significant larger sinus of Valsava and tubular part of aortic root than patients with normotension. We reported a normal reference value for aortic root size in Thai population. The aortic root sizes are influenced by hypertensive status, age and gender.